The Effect of Sustainability Reporting Practices on Environmental Performance in Manufacturing Firms Listed on the Indonesia Stock Exchange from 2018 to 2022 - Gianina Geralda Ginting; Susi Sarumpaet (International Journal of Economics, Commerce, and Management, 2025)
Sustainability reporting has been increasingly popular in recent years as businesses become more aware of environmental challenges. 96% of the top businesses in the world have implemented sustainability reporting practices, according to a KPMG survey. The effect of sustainability reporting practices on environmental performance is examined in this study. Sustainability reports, the implementation of GRI standards, and external assurance are used to gauge sustainability reporting procedures; firm size is used as a control variable. In this study, 305 observational data from manufacturing firm over a five-year period (2018-2022) were analysed quantitatively using binary logistic regression. The findings indicate that while the use of GRI standards has a positive and significant effect on environmental performance, sustainability reports and external assurance have no significant effect. These findings show that the implementation in GRI standards encourages business commitment to sustainable practices and transparency, both of which have a significant impact on environmental performance. In the meanwhile, external assurance and sustainability reports tend to be mostly symbolic and do not demonstrate a real commitment to environmental improvement. Environmental performance is positively impacted by the control variable, firm size. These findings suggest that a company's environmental performance is correlated with its size. As a control variable, firm size contributes to maintaining and clarifying the relationship between environmental performance and sustainability practices while ensuring objective and valid study findings. This study emphasizes the importance of strengthening the quality of sustainability reporting and expanding the application of external standards and assurance to improve the credibility and accountability of corporate environmental performance in Indonesia.